HR ANALYTICS: WHY IT MATTERS - Ekka, Susmita (The journal of contemporary issues in business and government, 2021)
In today‟s data driven world, HRM strategies are changing in terms of HR metrics and HR analytics being used in the organization for better decision making. This digitalization will help the organization to become more reliable towards data driven decision making rather than intuition. Which can assist organizations to take up present strategic and operational data and turn it into an effective approach to the HR problems of tomorrow. HR analytics has become a significant instrument for achieving success; taking advantage of present data to anticipate future ROI as a source of strategic advantage. The current study is an attempt to give an overview of developments in HR analytics at present by briefly focusing to identify the shift in the HR roles in different perspective. This paper also discusses the importance of understanding the implications of HRA. In addition, article also highlighted the future need for HR analytics, befitting for today‟s world of business industry.